Esensi Bertuhan Dalam Pandangan Metafisika Islam - Fahrizal Fahrizal; Syarifuddin Syarifuddin (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2024)
Abstract: Discussion of the Spirit is a discussion that cannot be separated from metaphysics. Metaphysics is a part of the philosophy of science that studies behind reality. Metaphysics is a part of philosophy about the nature behind physics (which appears). In reality, the concept of divine metaphysics is not well understood by adherents of the monotheistic sect themselves, even by Muslims themselves. Muslims, as well as adherents of this monotheistic sect, are still fixated on the concept level explicitly and not implicitly, so that much is understood using reason (aqli) and not with the soul (naqli). This causes the spirit of monotheism among Muslims and adherents of monotheism to be doubted, thereby affecting their ability to reflect monotheism in their environment, so that enlightenment regarding monotheism is reduced. This research aims to find out and analyze how to increase monotheism among Muslims and also adherents of monotheism themselves. The research method applied is descriptive qualitative with documentation studies, where the data collection technique uses documentation studies. In accordance with the results of existing research, it can be concluded that there are several ways to introduce the teachings of monotheism to Muslims and adherents of the monotheism sect, where these methods are by carrying out religious and theological education, socializing the values of monotheism, practicing worship. consistently, studying the Qur'an and hadith, increasing awareness and cleanliness of the heart, avoiding heresy and heresy, explaining monotheism on social media and da'wah, as well as conducting religious discussions and dialogue. Keywords: The essence of god in Islamic metaphysics. Abstrak: Pembahasan tentang Roh adalah pembahasan tidak terlepas dari metafisika. Metafisika adalah bagian dari filsafat ilmu yang memperlajari di balik realitas. Metafisika merupakan bagian falsafah tentang hakikat yang ada di balik fisika (yang nampak). Dalam kenyataannya konsep metafisika ketuhanan ini kurang dipahami oleh penganut aliran tauhid itu sendiri, bahkan oleh umat Islam itu sendiri. Umat Islam, maupun penganut aliran tauhid ini masih terpaku dalam tataran konsep secara tersurat dan bukan tersirat, sehingga banyak dipahami dengan menggunakan akal (aqli) dan bukan dengan jiwa (naqli). Hal ini menyebabkan jiwa ketauhidan seseorang dari umat islam dan juga penganut tauhid masih diragukan, sehingga mempengaruhi kemampuan mereka dalam merefleksikan ketauhidan di lingkungan mereka, sehingga pencerahan mengenai ketauhidan menjadi berkurang. Penelitian ini bertujuan untuk mengetahui dan menganalisa bagaimana cara meningkatkan ketauhidan umat Islam dan juga penganut aliran tauhid itu sendiri. Adapun metode penelitian yang diterapkan adalah deskriptif kualitatif dengan studi dokumentasi, dimana teknik pengumpulan data dengan menggunakan studi dokumentasi. Sesuai dengan hasil penelitian yang ada, maka dapat disimpulkan bahwa ada beberapa cara yang dilakukan untuk memperkenalkan ajaran tauhid kepada umat Islam dan penganut aliran tauhid, dimana cara tersebut adalah dengan melaksanakan pendidikan agama dan teologi, melakukan sosialisasi terhadap nilai-nilai tauhid, melakukan praktek ibadah secara konsisten, studi al-qur’an dan hadits, meningkatkan kesadaran dan kebersihan hati, menghindari bid’ah dan kesesatan, menjabarkan tauhid di media sosial dan dakwah, serta melakukan diskusi dan dialog agama. Kata kunci: Esensi bertuhan dalam metafisika Islam.